2021
DOI: 10.1073/pnas.2011491118
|View full text |Cite
|
Sign up to set email alerts
|

Cell type-specific modulation of healthspan by Forkhead family transcription factors in the nervous system

Abstract: Reduced activity of insulin/insulin-like growth factor signaling (IIS) increases healthy lifespan among diverse animal species. Downstream of IIS, multiple evolutionarily conserved transcription factors (TFs) are required; however, distinct TFs are likely responsible for these effects in different tissues. Here we have asked which TFs can extend healthy lifespan within distinct cell types of the adult nervous system in Drosophila. Starting from published single-cell transcriptomic data, we report that forkhead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 77 publications
2
6
0
Order By: Relevance
“…The studies of other groups describe the beneficial effects of haloperidol on cry1 expression in GB cells, but these results obtained in cell culture suggest that the doses required to treat patients might be toxic; in consequence, specific delivery strategies combined with haloperidol are worth of study. In addition, we observed significant effects of cry knockdown in normal glial cells, in line with Bolukbasiet al, who recently described the extension of lifespan by foxo upregulation in glial cells [46]. We observed an effect of cry upregulation in the number of glial cells (Figure 5L).…”
Section: Discussionsupporting
confidence: 90%
“…The studies of other groups describe the beneficial effects of haloperidol on cry1 expression in GB cells, but these results obtained in cell culture suggest that the doses required to treat patients might be toxic; in consequence, specific delivery strategies combined with haloperidol are worth of study. In addition, we observed significant effects of cry knockdown in normal glial cells, in line with Bolukbasiet al, who recently described the extension of lifespan by foxo upregulation in glial cells [46]. We observed an effect of cry upregulation in the number of glial cells (Figure 5L).…”
Section: Discussionsupporting
confidence: 90%
“…But these results obtained in cell culture suggest that the doses required to treat patients might be toxic, in consequence specific delivery strategies combined with haloperidol are worth of study. We have observed significant effects cry knockdown in normal glial cells, in line with Bolukbaso and cols that recently described the extension of lifespan by foxo upregulation in glial cells (Bolukbasi et al 2021). We have observed an effect of cry RNAi expression in the number of glial cells (Figure 5L).…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, CNS-speci c deletion of FoxO3 in 5xFAD mice led to altered brain lipid levels and exacerbation of synaptic loss and Abeta pathology, whereas astrocytespeci c overexpression of FoxO3 reversed these neurodegenerative phenotypes, suggesting a neuroprotective role of FoxO3 (Du et al, 2021). The single-cell RNA-sequencing (RNA-seq) pro ling of the adult Drosophila brain also showed that FOXO is endogenously expressed in glia but not neurons (Bolukbasi et al, 2021;Davie et al, 2018). Our study, together with published data, supports the role of the evolutionarily conserved IIS-FOXO pathway in regulating brain lipid metabolism, organismal health and life span.…”
Section: Discussionmentioning
confidence: 99%